Genetic potential of BR 5011-Sertanejo maize cultivar in the coastal plainlands of the northern region of Brazil - Carvalho, Helio Wilson Lemos de; Leal, Maria de Lourdes da Silva; Santos, Manoel Xavier dos; Pacheco, Cleso Antonio Patto (Pesquisa Agropecuaria Brasileira, 2000)
Five selection cycles were carried among and within half-sib progenies on the cultivar BR 5011-Sertanejo in the Counties of Neópolis (1991 and 1992), Neópolis and Umbaúba (1993), Lagarto (1994) and Neópolis, Lagarto and Cruz das Almas (1995), located in the Coastal Plainlands of the Northern region of Brazil. The study aimed to obtain a more yielding and well adapted cultivar of maize to the soil and climatic conditions of this region. The progenies were evaluated in lattice 14x14 with two replications. Recombinations of the outstanding progenies were processed within the same year in order to get one cycle per year. The magnitude of the genetic variability of the BR5011-Sertanejo cultivar was approximately the same in the cycles VI, VII and IX, conducted in one location. However, a reduction of this variability was observed in the cycles VIII and X, performed in more than one locality, since the estimatives obtained were less influenced by the interaction progeny x local, showing the importance of the selection in more than one environment, to increase the efficiency of the process and to obtain more accurate estimates of the genotypic variances. In relation to year yield the average gain estimated per selection cycle was 12.68% which associated to the high genetic variability presented by the cultivar and to the high average of progenies productivity indicates its potential for the continuation of the breeding program.